The role and features of peer assessment feedback in college English writing - Sun, Qiyu; Chen, Fang; Yin, Shengkai (Frontiers in Psychology, 2023)
Peer assessment is a common pedagogical practice for evaluating students’ writing in college English classrooms. However, in-depth research on the learning outcomes after peer assessment is scarce and inconsistent; how peer feedback is used has not been fully explored either. This study compared peer feedback to teacher feedback and explored the different features of feedback and its impact on draft revision. Two specific research questions were answered in this study: (1) In which aspects can peer feedback supplement teacher feedback in improving the linguistic features in writing? (2) What are the differences in features of peer feedback versus teacher feedback? And how do they connect to feedback take-in? Two writing tasks were assigned to 94 students. One received teacher feedback and the other peer feedback. Pre-feedback and post-feedback writings in both tasks (4 sets in total) were scored and human ratings were adjusted using Many-Facet Rasch modeling to control for differences in leniency. Drawing on three natural language processing (NLP) tools, this study also assessed writing qualities by comparing 22 selected indices related to the scoring rubrics for human raters, which involve three dimensions: cohesion, lexical quality and syntactic complexity. Peer and teacher feedback was then coded based on features of feedback to explore their influence on draft revision. The results showed that both peer and teacher feedback had positive effects on rating scores. We confirmed peer feedback as an effective classroom approach to improve writing, though limited compared to teacher feedback as reflected in the indices. In terms of feedback features, students often stopped at identifying the language problems, while the teacher provided more explanations, solutions or suggestions regarding the problems identified. Implications for peer feedback research and implementation of peer assessment activities are provided.